Physicochemical characterisation of remineralised dentine treated with self-assembling peptide p11-4 and chloro calcium phosphosilicate bioglass in saliva of obese children with severe dental caries in Saudi Arabia - Dawasaz, Ali Azhar (2025)
The recent trend in caries prevention is regenerative dentistry through biomineralization and growth of hydroxyapatite crystals. Calcium and phosphate ions in the saliva contribute to prevent demineralization and promote remineralization. Saliva is arguably the most accessible biofluid providing significant insights into an individual's health status. Nuclear magnetic resonance (1H-NMR) is highly effective for analysing mixtures and has been successfully utilised in investigations of metabolites within biofluids that necessitate minimal or no sample preparation. Paediatric obesity has been on the rise globally mainly due to excessive intake of processed foods. In obese children, the data on the metabolite profile and how the saliva influences the physical and chemical characteristics of regenerative biomaterials is still lacking. Thus, the aims of this study were to analyse and compare the salivary metabolite profiles of obese children with those of normal weight children, and to assess the effects of their saliva on the remineralising efficacy of self-assembling peptide P11-4 and chloro calcium phosphosilicate (CCPS) bioactive glass on artificially induced dentinal caries. This study comprises three steps. Experiment 1 includes collection of saliva of 20 obese and 20 normal weight children and analysing their metabolite content using 1H-NMR analysis. Experiment 2 includes application of P11-4 peptide and chloro calcium phosphosilicate on artificially induced dentinal caries sections. Experiment 3 involves immersing the treated dentinal sections of the teeth in saliva of patients collected in experiment 1 for 28 days. Their efficacy was assessed using scanning electron microscopy, energy dispersive X-ray spectroscopy and microcomputed tomography. Thirteen (3 amino acids, 4 carboxylic acids, 2 ketoacids, 1 alcohol and 3 miscellaneous metabolites) out of the 38 metabolites identified in normal and obese children with severe dental caries, had high VIP score. Glutamine and succinylacetone showed the highest VIP score with eight metabolites significantly increased in the saliva of obese children. Normal weight children had salivary Ca levels of 3.24±1.27 mg/dl and obese children had 2.37±0.858 mg/dl (p=0.016). Salivary P was 10.67±2.125 mg/dl and 8.88±2.729 in normal weight and obese children, respectively (p=0.027). After 7-days of treatment of dentin discs, P11-4 in normal children saliva was more efficient than other groups whereas after 28-days, CCPS in normal children saliva showed the best results. The outcome of this study would help in determining the clinical longevity of these therapies and in the long run, will pave way in developing a better protocol for the management of dentinal caries.